Hubungan Nilai PH Cairan Pleura dengan Hasil Pleurodesis pada Penderita Efusi Pleura karena Keganasan: [Acidity of Pleural Fluid and Pleurodesis in a Patient with Malignant Pleural Effusion] - Isnin Anang Marhana; Asep Tri Handoko (Jurnal Respirasi, 2017)
Background: Pleural effusion is a frequent complication of advanced stage are obtained in patients with malignancy. Shortness of breath at rest and decreased exercise tolerance are major functional limitations for patients with cancer who develop extensive pleural effusion. Pleural fluid drainage followed by a pleurodesis can reduce the symptoms of shortness of breath and prevent pleural fluid reaccumulation. Unfortunately, pleurodesis attempts fail in 10 to 40% of patients with recurrent pleural fluid and shortness of breath. Low pleural fluid pH can be used as a marker for increased metabolic activity of tumors in intrapleura, and is associated with increasing tumor, and can predict the failure of pleurodesis. The purpose of this study was to prove association between low pleural fluid pH value with failure pleurodesis in patients pleural effusion malignancy. Method: This is an observational study with cross sectional design that is the analysis conducted at Hospital Dr Soetomo in patients pleural effusion malignancy were subjected to pleurodesis for 6 months. Total 11 patients who meet the inclusion and exclusion criteria. Result: The mean value obtained pleural fluid pH 7,3±0,2, based on logistic regression analysis obtained low pleural fluid pH is not significant association with failure of pleurodesis, as shown from the significant value generated wald test is 0,116 where the value is above 0,05. Conclusion: Low pleural fluid pH is not significant association with failure of pleurodesis.